Nghiên cứu tác dụng xúc tác của phức paladium cố định trên chất mang nano từ tính (CoFe2O4) trong phản ứng ghép đôi HECK - Nam, Phan Thanh Sơn; Hương, Nguyễn Thị Thuỵ (Vietnam Journal of Chemistry, 2012)
Cobalt superparamagnetic spinel ferrite (CoFe2O4) nanoparticles were synthesized following a microemulsion method, and functionalized via silane chemistry with 3-(trimethoxysilyl)-propylamine to create surface amino groups. The amino-functionalized magnetic nanoparticles were allowed to react with 2-hydroxybenzaldehyde or 2-acetyl pyridine to form immobilized bidentate ligands, which were complexed with palladium acetate, affording the immobilized palladium complex catalysts with a palladium loading of 0.26 mmol/g and 0.33 mmol/g (AAS), respectively. The catalyst was characterized by X-ray powder diffraction (XRD), transmission electron microscope (TEM), thermogravimetric analysis (TGA), Fourier transform infrared (FT-IR), and elemental analysis (EA). The immobilized palladium complex was used as an efficient heterogeneous catalyst for the Heck cross-coupling reaction of iodobenzene and styrene to form stilbene as the principal product. Recovery of catalyst was facilely achieved by simple magnetic decantation. The immobilized palladium complex catalyst could be reused without significant degradation in catalytic activity.